Book Review - Juswara, Lina Susanti (REINWARDTIA, 2013)
H. J. Chowdhery & D. K. Agrawala. 2013. A century of West Himalayan Orchids. Bishen Singh Mahendra Pal Singh. New Connaught Place, Dehra Dun, India. 318 pp. Price USD 74.95